ORGANIZATIONAL INERTIA AND ORGANIZATIONAL PERFORMANCE: FAMILY BUSINESS CONTEXT IN INDONESIA - Intan Ramadania Hartono Putri; Tiffany Angwar; Metta Padmalia; Teofilus Teofilus (Universitas Pelita Harapan, 2022)
This research focuses on the fast-growing family business in Indonesia. The purpose of this study is to discuss the performance of family companies that are in a state of inertia, where Top Management Team (TMT), namely the executive ranks of the company's leaders is needed to influence the management of cynicism to commitment to move in organizational change. The theory of leadership by comparing the perception of ideal change in organizations is the reference we use, namely the implicit change leadership theory (ICLT). This research method uses a non-probability sampling method where the probability of being selected as a sample is not the same. The sampling technique used was purposive sampling and qualitative analysis of the organizational performance points of 31 family companies in Indonesia. The findings show that the paternalistic attitude of family culture reflects the commitment of TMT to make changes and performance that supports the company's success to move from inertia. The novelty in the article is the relationship of TMT in family businesses that supports the role of change through strong commitment, so that cynicism in family companies does not have a significant effect on organization. Abstrak dalam Bahasa Indonesia. Penelitian ini berfokus pada bisnis keluarga yang berkembang pesat di Indonesia. Tujuan dari penelitian ini adalah untuk membahas kinerja perusahaan keluarga yang sedang dalam keadaan inersia, dimana Top Management Team (TMT) yaitu jajaran eksekutif pimpinan perusahaan sangat dibutuhkan untuk mempengaruhi sinisme manajemen terhadap komitmen untuk bergerak di perubahan organisasi. Teori kepemimpinan dengan membandingkan persepsi perubahan ideal dalam organisasi adalah acuan yang kami gunakan, yaitu teori kepemimpinan perubahan implisit (ICLT). Metode penelitian ini menggunakan metode non-probability sampling dimana probabilitas terpilihnya sebagai sampel tidak sama. Teknik pengambilan sampel yang digunakan adalah purposive sampling dan analisis kualitatif terhadap poin-poin kinerja organisasi 31 perusahaan keluarga di Indonesia. Temuan menunjukkan bahwa sikap paternalistik budaya keluarga mencerminkan komitmen TMT untuk melakukan perubahan dan kinerja yang mendukung keberhasilan perusahaan untuk beranjak dari inersia. Kebaruan dalam artikel tersebut adalah hubungan TMT dalam bisnis keluarga yang mendukung peran perubahan melalui komitmen yang kuat, sehingga sinisme dalam perusahaan keluarga tidak berpengaruh signifikan terhadap organisasi.